Comparison of Working Memory, Cognitive Flexibility, and Sustained Attention in People with Previous COVID-19 Infection Who Have Recovered with Non-Infected Counterparts - Faezeh Sarabadan; Somayeh Pour Mohammadi (Patient Safety and Quality Improvement Journal)
Introduction:Many people experience persistent cognitive problems after COVID-19, with no current targeted treatments. This study compared working memory, cognitive flexibility, and attention in recovered COVID-19 patients versus non-infected peers to better understand these deficits.Materials and Methods: The study utilized a case-control and causal-comparative research design to explore cognitive differences related to COVID-19 severity. The participants were residents of Tehran divided into two groups: individuals who had not been affected by COVID-19 or experienced only mild cases, and those who had suffered from severe COVID-19 in 2023. The total sample consisted of 60 participants, with equal groups of 30 each, selected through convenience sampling. The methodology involved administering various memory assessments, including the N-Back, Wisconsin, and continuous performance tests, to evaluate cognitive function. For data analysis, an independent samples T-test was conducted in SPSS version 26 to compare cognitive performance between groups. Results: The recovered COVID-19 group had an average age of 40.57, while controls averaged 36.57. They scored lower in working memory (30.21 vs. 32.56, p=0.038) and cognitive flexibility (4.03 vs. 5.03, p=0.031). No significant differences were found in sustained attention, indicating it may remain unaffected post-recovery.Conclusion:COVID-19 recovery is linked to declines in working memory and flexibility. Interventions targeting these areas could aid recovery and improve quality of life. These differences were observed through measures of performance levels and survival rates. Based on these findings, it is recommended that interventions aimed at improving working memory and cognitive flexibility be implemented in hospitals and mental health centers.